Descriptive Inquiry at the Margins - Cioè-Peña, María (Schools (Chicago, Ill.), 2022)
In this autoethnographic article, I describe the ways in which I have used and adapted Descriptive Inquiry and the descriptive processes to further understand and support the needs of marginalized populations across three settings: a bilingual special education classroom in an urban school district, a research study with Spanish-dominant mothers, and a professional learning community in a racially integrated suburban school district. Using each setting, this article will describe the way Descriptive Inquiry and the processes have been adapted for use within (1) multitiered support systems for multiply marginalized learners, (2) research studies to elicit narratives from adult participants, and finally, (3) professional learning communities to unpack and understand teacher and student positionality in cross-racial relationships. Throughout the article, I show these adaptations/modifications were in keeping with Patricia Carini's and Descriptive Inquiry's core values and beliefs. The article closes with thoughts on how to honor, sustain, and grow Carini's work while also attending to issues of injustice and inequity in education.